AVALIAÇÃO DA QUALIDADE DE VIDA NO PRÉ E PÓS OPERATÓRIO DE CIRURGIA BARIÁTRICA EM OBESOS MÓRBIDOS - NETO, Larissa Sawaris; SOUZA, José Carlos; BASMAGE, João Pedro Teixeira; GHADIE, Samer Majid; LEITE, Lucas Rasi Cunha (ANAIS DO ENIC, 2018)
-